2009
DOI: 10.7202/019821ar
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages d’algues et relations avec quelques paramètres environnementaux dans deux sites marécageux de l’Ouest-Cameroun

Abstract: Résumé Les échantillons destinés à l’étude des algues ont été prélevés par grattage sur différents types de substrats et par expression de macrophytes immergées dans deux sites marécageux situés dans la région Ouest du Cameroun. Les observations au microscope optique ont permis d’observer les organismes encore vivants dans leur déplacement et de noter des détails qui pourraient disparaître du fait de la fixation. Les comptages ont été faits suivant des transects verticaux choisis au hasard sur la lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
2
1
Order By: Relevance
“…This abundance (31.33x105 cell/l) compared to other groups of micro-algae was in line with other works which showed that rivers of Cameroon (Nyong included) are richer in Chlorophyta species (Nguetsop et al, 2009;Mama et al, 2016).The limnohalin character of the estuary (mean salinity<5‰) justifies that fresh waters prevail over marine waters (Ayissi, 2014).The dominance of the genus Closterium (Chlorophyta) with 2.75x10 5 cell/l, and species Botryococcus braunii (Chlorophyta) with 3.98x10 5 cell/l and Calothrix brevissima (1.88x10 5 cell/l) and the presence of Cyanophyta group indicates an excess of nutrients in the environment which is the major characteristic of eutrophic ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…This abundance (31.33x105 cell/l) compared to other groups of micro-algae was in line with other works which showed that rivers of Cameroon (Nyong included) are richer in Chlorophyta species (Nguetsop et al, 2009;Mama et al, 2016).The limnohalin character of the estuary (mean salinity<5‰) justifies that fresh waters prevail over marine waters (Ayissi, 2014).The dominance of the genus Closterium (Chlorophyta) with 2.75x10 5 cell/l, and species Botryococcus braunii (Chlorophyta) with 3.98x10 5 cell/l and Calothrix brevissima (1.88x10 5 cell/l) and the presence of Cyanophyta group indicates an excess of nutrients in the environment which is the major characteristic of eutrophic ecosystems.…”
Section: Discussionsupporting
confidence: 92%
“…This difference observed can be due to the longer retention time and the bigger size of ponds as also indicated by Mara (2003) who showed that WSP pond ecology and performance depend on the pond geometry and size which impacts on the hydraulic. Also, the WSP species richness was lower than that obtained by Nguetsop et al (2009) who found for two natural oligotrophic wetlands of the West Cameroon Highlands an average of 20 species. This can be due to the fact that algal diversity in wetlands reduces with the increase of pollution up to a certain level as the hyper-eutrophication gradually reduces algae population in favour of macrophytes and land instalment (Short et al, 2007).…”
Section: Algal Diversity and Distributioncontrasting
confidence: 80%
“…20 L) was filtered through plankton net with a 40 µm mesh opening according to Groga [6]. After obtaining the filtrate, a volume of 250 mL of phytoplankton concentrate was introduced into well-labelled containers and fixed with 5% formalin in the proportions of ¾ of the sample and ¼ of formalin as recommended by Nguetsop et al [20] for quantitative and qualitative examinations.…”
Section: Phytoplankton Samplingmentioning
confidence: 99%
“…After homogenization of the phytoplankton concentrate in the laboratory, a 10 µL sample was taken using a micropipette and mounted on a slide for qualitative examination of phytoplankton species. For each sample, three slides were prepared to ensure reproducibility [20]. The identification of the phytoplankton taxa was made with a 40X objective of an optical microscope following vertical transects chosen at random using plates and identification keys [21][22][23][24][25].…”
Section: Qualitative and Quantitative Analysis Of Phytoplanktonmentioning
confidence: 99%